2001
DOI: 10.1021/ja004023p
|View full text |Cite
|
Sign up to set email alerts
|

Differential Rates of Reversibility of Ecteinascidin 743−DNA Covalent Adducts from Different Sequences Lead to Migration to Favored Bonding Sites

Abstract: Ecteinascidin 743 (Et 743), one of a series of structurally related antitumor antibiotics isolated from a marine tunicate, is currently in phase II clinical trials. Et 743 alkylates guanine N2 through the minor groove of DNA. Hydrogen-bonding networks that associate the drug with a three base pair DNA recognition site have been proposed to contribute to both the reactivity and the stability of the Et 743-DNA adduct. Here, we report that the reaction of Et 743 with DNA is reversible under nondenaturing conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 21 publications
1
77
0
Order By: Relevance
“…The substrates were constructed by ligating a duplex oligonucleotide modified with Et 743 at a single guanine to flanking duplex oligonucleotides on both the 5 0 -and 3 0 -sides. Although we succeeded at creating a site-directed adduct at a 5 0 -AGC sequence, attempts at generating a site-directed adduct at the 5 0 -AGT sequence failed [30]. After several ligation and purification steps, it was observed that the ligated 60-mer no longer contained Et 743 covalently bound at the 5 0 -AGT sequence.…”
Section: 8mentioning
confidence: 99%
See 2 more Smart Citations
“…The substrates were constructed by ligating a duplex oligonucleotide modified with Et 743 at a single guanine to flanking duplex oligonucleotides on both the 5 0 -and 3 0 -sides. Although we succeeded at creating a site-directed adduct at a 5 0 -AGC sequence, attempts at generating a site-directed adduct at the 5 0 -AGT sequence failed [30]. After several ligation and purification steps, it was observed that the ligated 60-mer no longer contained Et 743 covalently bound at the 5 0 -AGT sequence.…”
Section: 8mentioning
confidence: 99%
“…A band shift assay was used to monitor the amount of drug-modified duplex in order to determine if the covalent adduct is stable over time [30]. A 22-mer oligonucleotide containing a single modification site, either 5 0 -AGT or 5 0 -AGC, surrounded by a common sequence (Fig.…”
Section: 8mentioning
confidence: 99%
See 1 more Smart Citation
“…Given the amount of nonpolar surface area that is buried upon complex formation (ϳ525 Å 2 ), we would expect an important hydrophobic contribution not only to the free energy of trabectedin-DNA association but also to the ensuing stabilization of the double helix in the aqueous medium. For a complex of the type reported here it seems safe to assume that the increase in the temperature of DNA thermal denaturation will be larger than that obtained for a DNA oligonucleotide containing a single trabectedin adduct, which has been shown to be of 19°for a 5Ј-AGC site (Zewail-Foote and Hurley, 2001a). Therefore, it is not unreasonable to think that the known ability of trabectedin to block the activity of exonuclease III (ExoIII) (Dziegielewska et al, 2004) or the helicase activities of both the simian virus 40 (SV40) large tumor antigen (T-antigen) (Zewail-Foote and Hurley, 2001a) and the UvrA 2 B complex (Zewail-Foote and Hurley, 2001b) derives from this substantial stabilization, which is likely to be amplified if two or more suitable triplets are tandemly or separately arranged in the oligonucleotide sequence.…”
Section: Discussionmentioning
confidence: 77%
“…The stability of these complexes is governed by DNA target sequences, since under some conditions the drug is not capable of forming optimally stable bonds with its corresponding recognition sites in the DNA leading to the formation of unstable products. The same authors in other work (25) demonstrated that ET-743 can migrate from a nonfavored bonding sequence (5Ј-AGT) to the favored sequence site (5Ј-AGC) and that the ET-743-AGT adduct is less stable, displays a higher degree of molecular motion, and produces dif- ferent conformational changes in DNA than the more stable alkylation product ET-743-AGC.…”
Section: Col1a1 Promoter Activity Is Affected By Et-743 In Stablymentioning
confidence: 86%